QAWAID TAFSIR: TELAAH ATAS PENAFSIRAN AL-QUR’AN MENGGUNAKAN QAUL SAHABAT - Rosyad, Aftonur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
The emergence of a wide variety of interpretations of the Qur’an methodology often forget the methods offered by the classical scholars. Though the appearance of the existing methods of interpretation as it is today can not be separated from the rules of interpretation which was initiated by the classical scholars of the period. The Qur'an as a book of guidance for human beings can not be understood directly without the rules of interpretation that apply. One of the rules of interpretation used in interpreting the Qur'an is a rule of interpretation of the word friend. The interpretation of the word friend is regarded as highly representative explanation of the validity of the understanding of the Qur'an. Because friends are people that are still able to meet directly with the Prophet, of course, the rules of interpretation that are used are not much distorted.